1972
DOI: 10.1159/000213979
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-Neutralizing Factor (Platelet Factor 4) from Human Blood Platelets and its Reactivity with Fibrinogen and Soluble Fibrin-Monomer Complexes

Abstract: The heparin-neutralizing factor (PF4) has been isolated from the supernatant of thrombin-treated, washed human blood platelets. The major part of the factor is present as a PF4-proteoglycan complex which can be dissociated at higher ionic strength. PF4 thus obtained is a basic protein of molecular weight 29,700. The carrier proteoglycan will recombíne with a maximum of 4 molecules of PF4, whereby dimerization of the resulting complex is observed. This is in contrast to the naturally occurring, released complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

1974
1974
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
(26 reference statements)
1
2
0
Order By: Relevance
“…The PF4 and PTG purified in this laboratory were homogeneous on SDS polyacrylamide gels and had amino acid compositions which were similar to the preparations from other laboratories (Deuel etal, 1977;Handin & Cohen, 1976;Kaser-Glanzmann et al, 1973;Levine & Wohl, 1976;Morgan et al, 1977;Moore et al, 1975b;Nath et a / , 1975). The radioimmunoassays which have been developed for PF4 and PTG are sufficiently sensitive to measure the levels in normal plasma as described in the literature: for PTG 19i-7.5 ng/ml (Ludlam et al, 1975) and for PF4 13 k0.55 ng/ml, range 2-23 ng/ml (Bolton e t a / , 1976a) and 16 & 4 ng/ml determined by radioimmunoassay, 720 & 920 ng/ml (Nicwiarowski et a / , 1976) by immunodiffusion, and 0.085 U/ml, range 0.08-0.089 U/ml (Gjesdal, 1974) by electroimmunoassay which would be equivalent to 500 ng/ml, range 471-424 ng/ml based on the specific activity of his standard PF4 which was 170 U/mg.…”
Section: Discussionsupporting
confidence: 69%
“…The PF4 and PTG purified in this laboratory were homogeneous on SDS polyacrylamide gels and had amino acid compositions which were similar to the preparations from other laboratories (Deuel etal, 1977;Handin & Cohen, 1976;Kaser-Glanzmann et al, 1973;Levine & Wohl, 1976;Morgan et al, 1977;Moore et al, 1975b;Nath et a / , 1975). The radioimmunoassays which have been developed for PF4 and PTG are sufficiently sensitive to measure the levels in normal plasma as described in the literature: for PTG 19i-7.5 ng/ml (Ludlam et al, 1975) and for PF4 13 k0.55 ng/ml, range 2-23 ng/ml (Bolton e t a / , 1976a) and 16 & 4 ng/ml determined by radioimmunoassay, 720 & 920 ng/ml (Nicwiarowski et a / , 1976) by immunodiffusion, and 0.085 U/ml, range 0.08-0.089 U/ml (Gjesdal, 1974) by electroimmunoassay which would be equivalent to 500 ng/ml, range 471-424 ng/ml based on the specific activity of his standard PF4 which was 170 U/mg.…”
Section: Discussionsupporting
confidence: 69%
“…22,64 Both bovine and human PF4 are tetrameric. 36 The subunit is a single polypeptide chain. The molecular weight of the subunit has been reported to be 7800 to 12,000 daltons, depending on the species.…”
Section: The Purification and Characterization Of Pf4mentioning
confidence: 99%
“…According to Niewiarowski et a1 (1968) platelet factor 4 is the constituent in platelets responsible for inducing non-enzymatic 'paracoagulation'. However, the studies of Kaser-Glanzmann et al (1973) show that the originally observed effect of platelet factor 4 in precipitating soluble fibrin is caused by zinc impurities in the platelet factor 4 preparation of Niewiarowski et a1 (1968). In spite of that, further basic proteins capable of inducing the paracoagulation phenomenon (Koped et a1 1968) are located in the platelets and may be released after endotoxin injection.…”
Section: Discussionmentioning
confidence: 98%